Rancang Bangun Aplikasi Implementasi Ukiran Bali pada Objek Bangun Datar - I Kadek Erik Priyanto; I Ketut Gede Darma Putra; Ni Made Ika Marini Mandenni (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2017)
Carving art has an important role which is used as decoration of buildings, holy places in Bali and functional objects, but the efforts for cultural preservation still tend to be less. Tradition, decoration, and technology are the perfect combination to help preserve the variety of carving art, so that the application of Bali Carving Implementation in Two Dimentional Object is built. This application uses canvas which is an element of HTML that allows to manipulate bitmap area directly by using JavaScript. Library Fabric.js is used to simplify the manipulation of bitmaps on HTML5 canvas elements. Fabric.js allows the creation of objects, and image filters. Remove white is one filter that can be done. Remove white is used to remove white color, where the threshold value is used as the limit value of the application to remove the white color in the image so as to maximize the carving registration process on the application. The resulting application can be run on the browser and gives an illustration result of the carving implementation that can be saved in PNG file format.